ANALYSIS OF NONLINEAR DYNAMIC CHARACTERISTICS OF AN IMPACT-UNBALANCED SUSPENDED ROTOR SYSTEM - LIU JunJie; ZHANG LingYun; MA ShaoHui; LAN HaiPeng; ZHANG YouQiang (Jixie qiangdu, 2022)
Established an impact-unbalanced suspended rotor system mechanics models, and the dimensionless motion equation of system is deduced, using the fourth order Runge-Kutta method for the numerical calculation of this model, the integrated use of bifurcation diagram, orbit diagram, Poincare section diagram, the axis displacement time history diagram, maximum moment diagram and duty ratio diagram study the dynamic behavior of the system, identify the impact of the rotor, the maximum torque and impact by the proportion of time, and analyzed the speed ratio and the change of the stiffness coefficient of the influence of the nonlinear dynamic characteristics of the system.The analysis results show that the system presents chaotic motion in a certain parameter domain at the medium velocity stage, while the system tends to stable periodic motion in other parameter domains.With the increase of the stiffness coefficient, the chaotic motion region and the maximum moment of the system increase, and the stability of the system decreases.